2015
DOI: 10.1039/c5ra03602j
|View full text |Cite
|
Sign up to set email alerts
|

Ni/Mn ratio and morphology-dependent crystallographic facet structure and electrochemical properties of the high-voltage spinel LiNi0.5Mn1.5O4 cathode material

Abstract: The LiNi 0.5 Mn 1.5 O 4 (LNMO) spinel is an attractive cathode material for next generation lithium-ion batteries as it offers a high power capability with a discharge voltage of 4.7 V and a theoretical capacity of 147 mA h g À1 . In this paper, porous LNMO microspheres/cubes, which are constructed with nanometer-sized primary particles with different Ni/Mn ratios, have been synthesized by a facile method that involves the use of MnCO 3 microspheres/cubes as the self-supporting template. The effects of the mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 59 publications
(136 reference statements)
1
11
0
Order By: Relevance
“…It has been reported that the radius of Mn 3+ (0.645 Å) is larger than that of Mn 4+ (0.530 Å), so the lattice parameter increase of LNMO after LLAZO modifying is mainly caused by foreign ions migrating into the lattice of LNMO from coating layer, which could lead the transform of Mn 4+ to Mn 3+ . 67 In Figure S2, the Raman spectra of all materials were compared to investigate the local structure change of LNMO. According to previous studies, the peak located at 630 cm -1 could be attributed to the symmetric Mn-O stretching mode (A1g) in the MnO6 octahedron of LNMO.…”
Section: Sample Characterizationmentioning
confidence: 99%
“…It has been reported that the radius of Mn 3+ (0.645 Å) is larger than that of Mn 4+ (0.530 Å), so the lattice parameter increase of LNMO after LLAZO modifying is mainly caused by foreign ions migrating into the lattice of LNMO from coating layer, which could lead the transform of Mn 4+ to Mn 3+ . 67 In Figure S2, the Raman spectra of all materials were compared to investigate the local structure change of LNMO. According to previous studies, the peak located at 630 cm -1 could be attributed to the symmetric Mn-O stretching mode (A1g) in the MnO6 octahedron of LNMO.…”
Section: Sample Characterizationmentioning
confidence: 99%
“…Wan et al. had been reported that the enlarged lattice parameter a which was attributed to the highest Mn 3+ content and the ratio of Mn 3+ to Mn 4+ (Mn 3+ /Mn 4+ ) increases with the decrease of the Ni/Mn ratio in the samples. It further confirms that various Mn oxidation states influence the amount of Mn 3+ content and the configuration of Ni/Mn in the octahedral sites.…”
Section: Resultsmentioning
confidence: 66%
“…In order to figure out the content of Mn with different valence states in the as‐synthesized LNMO, the high‐resolution XPS measurements for the binding energy of the four samples and the fitted spectra of Mn 2p 3/2 peaks are plotted in Figure . The Mn 2p 3/2 peak in each sample can be well fitted to two components of Mn 3+ and Mn 4+ which also was reported in earlier research . The relative percent of manganese in different valence states calculated by peak area ratios are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that there may exist a phase transition in this range from spinel to layered structure, or a mixture of both two phases exist within this whole range. Whatever the case is, the layered phase structure has a severe risk of phase segregation for Mn content, since Li-Mn-O cannot stay stable in a layered structure 5,59,[122][123][124] . Such phase segregation may cause the electrode degradation and render the cycle life much shorter.…”
Section: Introductionmentioning
confidence: 99%